Predictors of Attrition from Care and Treatment Centres among HIV-positive Pregnant and Breastfeeding Adult Women in Dar es Salaam, Tanzania - Elias, Felix; Shaban, Nyimvua; Rutalebwa, Edwin (Tanzania Journal of Science, 2023)
In Tanzania, poor retention rates among pregnant and breastfeeding mothers continue to be a problem, contributing to a mother-to-child HIV transmission rate of 11% in 2019, compared to a global target of 5%. The goal of this study was to determine the influence of retention on clinical outcomes and identifying predictors of attrition among HIV-positive pregnant and breastfeeding women from follow-up care in Dar es Salaam. A retrospective cohort study included HIV-positive women who engaged in PMTCT services in public and private health facilities between January 2016 and December 2019. Secondary data were extracted from databases used for routine follow-up in care and treatment clinics (CTCs). The estimates of cumulative incidences of poor retention from date of enrollment or ART initiation were assessed using Kaplan–Meier method. The Cox regression model was used to identify the predictors of attrition. Among 20,225 HIV-infected pregnant and lactating women enrolled in PMTCT services, 93.35%, 89.07%, and 85.24% were classified as retained in care at 12, 24, and 36 months, respectively. The attrition rate at the end of the follow-up period was 15.82%, and WHO clinical stages 3 or 4 (aHR = 1.67, 95% CI: 1.46–1.89; p-value < 0.001) and unsuppressed viral load (aHR = 3.79, 95% CI: 3.20–4.49; p-value < 0.001) were predictors of increased risks of attrition. The maternal age group 25–34 years (aHR = 0.24, 95% CI: 0.18–0.32; p-value < 0.001), being married or cohabiting (aHR = 0.45, 95% CI: 0.38–0.55; p-value < 0.001), an efavirenz (EFV)-based regimen (aHR = 0.26, 95% CI: 0.19–0.35; p-value < 0.001), and good adherence to ART (aHR = 0.61, 95% CI: 0.48–0.79; p-value < 0.001) were factors associated with reduced risks of attrition. The study shows that a strong tracking system for lost to follow-up (LTFU), that is, patients who miss appointments to the same health facility for more than 3 months after the last scheduled clinical visit, should be prioritised for successive PMTCT programmes for better clinical outcomes. Keywords: Retention, Attrition, Treatment, Clinics, Loss-to-follow ups